Trespassing Cultural Boudaries in Audiovisual Media: Aboriginal Female Discourse and Cultural Heritage in Maïna - SASSO E (Padova University Press, 2021)
In the last decade, an interesting cultural phenomenon occurred in Canadian film as a result of the flowering of an indigenous Inuit cinema. In the so-called ‘cinema of minorities’ non-Inuit viewers are taken into a cultural and contextual limbo, where they find themselves positioned in a culture which they can hardly relate to and faced with legends they are not acquainted with. From this perspective, interlingual subtitling can be described as a foreignizing, or overt, type of translation since the foreign nature of the source text is foregrounded. This chapter takes as its starting point the conceptual metaphor ‘subtitling is cultural heritage’ in order to advance a new reading of subtitling, one which sees this medium as a new audio-visual narrative category which is able to preserve the ethno-cultural diversity in Canada. Such a film with subtitles as Maïna (2013) not only envisions its own detailed blueprints of Inuit communities, but is also an audio-visual narrative examining the relationship between media and minority cultures. All extra-linguistic geographical and ethnographic references such as limestone totems, string games, stone landmarks, oil lamps, igloos, facial tattoos, and throat songs are presented through a constant interaction between image (still and dynamic), language (speech), sound (sound effects) and music (performed). I intend to track through these references and look at the issues – the role of subtitling in the preservation of cultural specificity, subtitling strategies for rendering culture-bound terms, etc – which they raise. But my central purpose is to re-read the aforementioned film from a cognitive perspective projecting such a conceptual metaphor as ‘Inuit women are survival women’. I analyse the linguistics of subtitling in order to demonstrate that native femininity may be conceptualized in subtitling and that Inuit oral narratives are reproduced faithfully by audio-visual media. Through such an Inuit movie as Maïna (2013), I suggest, subtitling may be considered an ...